2017
DOI: 10.1111/dar.12582
|View full text |Cite
|
Sign up to set email alerts
|

Social inequality in youth violence: The role of heavy episodic drinking

Abstract: The findings lend support to both the differential exposure hypothesis and to the differential vulnerability hypothesis as well as the hypothesis of an enhancing effect of impulsivity on the HED-violence association. The SES difference in youth violence can be accounted for by: (i) an elevated prevalence of HED in low-SES groups; and (ii) a stronger than average link between HED and violence in low-SES groups due to their higher than average impulsivity score. [Norström T, Rossow I, Pape H. Social inequality i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Parents' educational level was our main indicator for socioeconomic background. Previous analyses of the data set showed that a relatively small group with low-educated parents differed markedly from those with medium-or high-educated parents with respect to drinking (Norström et al, 2017;Pape et al, 2017). Whether the parents' educational level was high or medium barely made a difference, implying that the main social divide was between the lowest parental education group and all the others.…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…Parents' educational level was our main indicator for socioeconomic background. Previous analyses of the data set showed that a relatively small group with low-educated parents differed markedly from those with medium-or high-educated parents with respect to drinking (Norström et al, 2017;Pape et al, 2017). Whether the parents' educational level was high or medium barely made a difference, implying that the main social divide was between the lowest parental education group and all the others.…”
Section: Methodsmentioning
confidence: 93%
“…Therefore, we distinguished between low educational level (one parent had vocational training, whereas the other had no post-compulsory education, or both had no post-compulsory education) (6%) and middle/high level (all others) (94%) in the present study. This dichotomous indicator of SES is identical to that used by Norström et al (2017). In addition, we applied a measure of parental marginal socioeconomic position, which was coded as "1" if at least one of the parents was an unemployed social welfare recipient (9%) and "0" otherwise (91%).…”
Section: Methodsmentioning
confidence: 99%
“…The violence we detected is perpetrated above all by the boys and men; between peer groups, through physical violence; or against the girls and women, harassing them and pressurising them sexually; and inside and outside romantic relationships through different forms of psychological and technological violence. Prior research had shown that violent behaviours are higher in boys and men than in girls and women (Norstr€ om, Rossow, & Pape, 2018), with the former being more likely to perpetrate physical and sexual aggressions (Shorey, Stuart, & Cornelius, 2011), whereas the latter have a greater risk of suffering harm related to alcohol (Huhtanen & Tigerstedt, 2012) harassment and frustration, pressure in unwanted situations, responsibility that is not sought and is inappropriate, psychological and physical harm (Enser, Appleton, & Foxcroft, 2016). In other contexts, results were in along the same lines; for example, in a study carried out by Davoren, Dahly, Shiely and Perry (2017) on alcohol consumption among university students, 65% of the men reported a hazardous alcohol consumption compared to 68% of women.…”
Section: Discussionmentioning
confidence: 99%
“…During full-text selection, outcome measures of violence and delinquency that included illegal activities or were stated in a way that did not preclude offences were kept. An example was a violence outcome measure that captured how many times the participant beat or kicked someone in the last 12 months (Norström et al, 2018).…”
Section: Selection and Review Processmentioning
confidence: 99%